2021
DOI: 10.1038/s41598-021-99923-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel temporary immersion bioreactor system for large scale multiplication of banana (Rasthali AAB—Silk)

Abstract: Musa sp. cultivar Rasthali (Silk AAB) is a choice variety of the Asian sub-continent. Its production and sustenance are threatened by Fusarium wilt, which affects the livelihoods of small and marginal farmers. The use of quality planting material is one of the strategies to manage the disease. Availability of quality planting material for varieties other than Grand Naine is limited. Large-scale micropropagation using existing technologies is laborious and expensive. Temporary immersion bioreactor system is eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 56 publications
5
19
0
Order By: Relevance
“…In this research, 10 and 20 mL/explant are shown to be the most suitable condition to increase the number and length of shoots and roots in C. palmata compared to volumes of 5 or 40 mL/explant which recorded the lowest averages. This same trend is reported by Uma et al (2021) in banana (Rasthali AAB-Silk) where a volume of 40 mL/explant of culture medium improves the number and length of shoots compared to 16 and 83 mL that evidence lower multiplication rates and shoot development, using a BIT system; likewise, Arano et al (2020) manage to increase the number and length of shoots with 25 or 50 mL/explant, whereas, a volume of 12.5 and 100 mL causes a decrease in the proliferation rate in C. esculenta. The ndings of this study show that a volume of 20 mL/explant of culture medium (200 mL) is the most suitable condition to increase the number of leaves and dry weight of C. palmata culture.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this research, 10 and 20 mL/explant are shown to be the most suitable condition to increase the number and length of shoots and roots in C. palmata compared to volumes of 5 or 40 mL/explant which recorded the lowest averages. This same trend is reported by Uma et al (2021) in banana (Rasthali AAB-Silk) where a volume of 40 mL/explant of culture medium improves the number and length of shoots compared to 16 and 83 mL that evidence lower multiplication rates and shoot development, using a BIT system; likewise, Arano et al (2020) manage to increase the number and length of shoots with 25 or 50 mL/explant, whereas, a volume of 12.5 and 100 mL causes a decrease in the proliferation rate in C. esculenta. The ndings of this study show that a volume of 20 mL/explant of culture medium (200 mL) is the most suitable condition to increase the number of leaves and dry weight of C. palmata culture.…”
Section: Discussionsupporting
confidence: 90%
“…It is evident that the number of shoots per explant is a function of longer immersion time (5 min). Similar trends are shown byRachmi et al (2019) andAlvarenga and Salazar (2015) who indicate that a prolonged immersion time is critical to increase the rate of shoot proliferation in Aquilaria malaccensis and S. rebaudiana, however, this immersion time is not always optimal to generate plant material of excellent morphological quality, since a prolonged immersion time can cause undesirable physiological disorders such as asphyxia, hyperhydricity and formation of reactive oxygen species, negatively affecting the quality of propagated plant material(Uma et al 2021). The results of this research show that a short immersion time (1 min) is the most suitable condition to increase shoot length, root system development, leaf number and crop dry weight.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The use of the highest density of explants that do not cause a diminution on growth increases the efficiency of nutrient uptake and laboratory space. The high inoculation densities can reduce the proliferation of the shoots and increase the contamination (Paek et al, 2001), but in some cases as Curcuma longa and banana the number of plants per bioreactor could be increased in a 50% percentage maintaining optimal growth responses (Marchant et al, 2021;Uma et al, 2021). In Cymbopogon citratus and hazelnut, the low explant density decreased the growth (Quiala et al, 2014;Nicholson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…4). The physicochemical parameters of the media represented nutrients used for explant metabolism in the TIB (Uma et al, 2021). Sufficient quantities of nutrients must be available for the optimal growth of all explant cells in the TIB.…”
Section: Sugarcane Callus Proliferation In Tib With Different Initial...mentioning
confidence: 99%